2014
DOI: 10.3109/15513815.2014.915365
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Anemia and Progressive Neurologic Impairment: Think About Triosephosphate Isomerase Deficiency

Abstract: We have reported the first Tunisian case of triosephosphate isomerase (TPI) deficiency in a 2-year-old girl. She was the first child of a nonconsanguineous couple. The disease included a neonatal onset of chronic hemolytic anemia, recurrent low-respiratory infections then progressive neurological involvement. The diagnosis was made after her death from the TPI values of her parents who exhibited intermediate enzyme deficiency. Molecular study of TPI genes showed that the father and the mother are heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In particular, a few patients showed neurological symptoms similar to those in the present patient, such as hemiplegic migraines (20,27,28), although the details of the clinical manifestations appear to be different. Dysfunction of some glycolytic enzymes other than PGK impairs not only for RBC but also for the CNS (29,30). The CNS may not tolerate minor glycolysis dysfunction better than the RBC, because the CNS requires substantial energy compared to RBC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a few patients showed neurological symptoms similar to those in the present patient, such as hemiplegic migraines (20,27,28), although the details of the clinical manifestations appear to be different. Dysfunction of some glycolytic enzymes other than PGK impairs not only for RBC but also for the CNS (29,30). The CNS may not tolerate minor glycolysis dysfunction better than the RBC, because the CNS requires substantial energy compared to RBC.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant E104D produces the most common form of human TIM deficiency. A case hemolytic anemia due to TIM deficiency E105D ( 103 ) has been recently reported . The crystal structure of wild type HsTIM was modeled in an attempt to explain the molecular basis of the TIM deficiencies with the E104D ( 103 ), G122R ( 121 ) and F240I (239 ) mutations .…”
Section: Effect Of Specific Residues At Selected Positionsmentioning
confidence: 99%
“…The neurologic development of our patients was normal during the first 8 months and then ceased to improve, especially during infection periods, and loss of acquired functions was subsequently observed. Aissa et al [ 2014 ] reported a girl with TPI deficiency who had distal weakness, respiratory failure, and chronic haemolytic anaemia, which was always triggered by recurrent bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%